Streptococcus zooepidemicus Infection in Sheep - Stevenson, R. G. (1974)
Fibrinous pericarditis, fibrinous pleuritis and pneumonia associated with Streptococcus zooepidemicus were observed in two lambs in a small flock of sheep. These lesions were reproduced in lambs inoculated intratracheally with Streptococcus zooepidemicus. Clinical signs included pyrexia, serous to mucopurulent nasal discharge, dyspnea and depression followed by death in six to seven days. Histologically the tissue changes were characterized by an acute inflammatory response involving bronchioles and alveoli, fibrinous pleuritis and fibrinous pericarditis.